Autonomy and responsibility in sexual assault law in NSW: The Lazarus cases. Issue 1 (2nd January 2019) - Mason, Gail; Monaghan, James
ABSTRACT: In 2007, significant reforms were made to the law of sexual assault in New South Wales, Australia. These reforms introduced communicative ideals into the physical and mental element of the offence of sexual assault. Ten years later, the first appellate decisions directly on these aspects of the reforms were handed down. These decisions are part of a suite of four cases emerging from the prosecution of a young man, Luke Lazarus, for the sexual assault of an 18-year-old woman in Sydney. This article analyses the judgments in these cases. It aims to provide insights into judicial thinking on key communicative aspects of sexual assault law in New South Wales, particularly the twin concepts of autonomy and responsibility that are embedded in the communicative model of consent. It argues that while there are encouraging signs of progress in judicial interpretation of women's sexual autonomy, there is reason to be concerned that law reform in this area may have had little impact when it comes to placing an expectation upon men to take responsibility for sexual communication.